The Christian Right in Europe: Movements, Networks, and Denominations (transcript Verlag, 2023)
Inspired by the success of the US Christian Right and the rise of the global far-right, ultraconservative Christians in Europe are joining forces and seek to reshape Europe. By assembling in anti-gender movements and sharing anti-Muslim narratives, they actively influence the political landscape and shape government policies. The contributors offer new perspectives on the protagonists and the entangled networks that work to abolish liberal democracy in Europe behind the scenes. This anthology is the first to bring together case studies on the Christian Right in over 20 European countries, providing a transnational perspective and an accessible insight for clergy, politicians, and academics alike.